2011
DOI: 10.1080/10643389.2010.495644
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Brain and Behavior Toxicity of Air Pollutants: A Focus on the Effects of Polycyclic Aromatic Hydrocarbons (PAHs)

Abstract: Because the developing brain is highly susceptible to toxic injuries, the effects of early exposure to air pollutants such as polycyclic aromatic hydrocarbons have to be questioned. In addition to direct inhalation, food consumption appears to be the main source of intake for these pollutants in humans. Thus, a risk does exist for newborns and young infants through ingestion of contaminated milk from their mothers or commercial ruminant preparations at a moment of extreme vulnerability for the brain. The autho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 79 publications
0
18
0
1
Order By: Relevance
“…These differences may be related to multiple factors including both variations in molecular structure, ways of metabolism, toxicokinetic characteristics, brain targets of interactions, way of administration and levels of exposure. Whereas BaP has been demonstrated to modify several functional endpoints in the brain including neuronal excitability, oxidative stress, and several neurotransmitter systems [7], little is known about the brain cellular and/or molecular toxicity of fluorene, requiring the testing of the effects of this compound [30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These differences may be related to multiple factors including both variations in molecular structure, ways of metabolism, toxicokinetic characteristics, brain targets of interactions, way of administration and levels of exposure. Whereas BaP has been demonstrated to modify several functional endpoints in the brain including neuronal excitability, oxidative stress, and several neurotransmitter systems [7], little is known about the brain cellular and/or molecular toxicity of fluorene, requiring the testing of the effects of this compound [30].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the potential neurotoxicity of PAHs has received much less attention despite some human and animal evidence (for review, see reference [7]). In humans, PAH-related neurological symptoms were reported in residents living near two dumping sites in Texas [8] or a waste oil reprocessing plant in California [9], and in workers of a coke processing plant in Poland [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main mechanism of these negative health effects was found to involve their effects on enzymes, especially on the cytochrome P450 (CYP) family of enzymes, including CYP1A [18,19,20,21]. Research has also shown that PAHs could be transferred from their mothers to newborns and young infants, and cause brain and behavior toxicity [1,22]. Moreover, the diet may be the major source of exposure to PAHs for people who are non-tobacco-smokers and non-occupationally exposed.…”
Section: Introductionmentioning
confidence: 99%
“…21 Regarding the specific effects of gestational PAH exposure on neurodevelopment in laboratory animals, potential mechanisms include impairment in N-methyl-Daspartate receptor-1 (NMDAR1) subunit expression and impaired long-term potentiation (LTP) generation (reviewed in ref 71).…”
Section: Figurementioning
confidence: 99%